Implementasi Kebijakan Pengawasan Badan Pengawas Pemilihan Umum (Bawaslu) Dalam Pemilihan Wali Kota Dan Wakil Wali Kota Kota Semarang Tahun 2020 - Afifah, Ulfatun Nur; Ni’am, Harun (Fakultas Ilmu Sosial dan Ilmu Politik Unwahas, 2023)
The 2020 election for Mayor and Deputy Mayor (Pilwalkot) of Semarang City was only attended by a single candidate pair, namely Hendrar Prihadi-Hevearita Gunaryanti Rahayu. Various potential vulnerabilities still occur, although they are different compared to if more than one pair of candidates participated. The supervisory policy of the Semarang City General Election Supervisory Agency (Bawaslu) is of course also based on this, guided by Law Number 10 of 2016 and technical instructions for each stage regulated in the perbawaslu. By using qualitative descriptive research and collecting datausing documentation and interview methods. This research uses George C. Edward III's policy implementation theory which has four indicators, namely communication, disposition, resources and bureaucratic structure. The research results show that in the process of implementing election supervision policies by Bawaslu in the 2020 election for mayor and deputy mayor of Semarang, things were supportive/positive in the four indicators used in the research process.Â